Consumer Preferences in Selecting Nail Art Products using Conjoint Analysis - Glorya Stephanie Quartine Sitompul; Sienatra, Krismi (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This research aims to explore consumer preferences regarding the attributes of price, durability, time, and nail design in the nail art business. We systematically collected and analyzed data using the quantitative research method and conjoint analysis tools. The research results indicate that durability is the most important attribute, followed by price, processing time, and nail design. Consumers prefer prices between Rp100,000 and Rp150,000, durability up to 3 months, a processing time of 60–90 minutes, and gradient nail designs color. This combination of attributes is considered ideal by consumers because it provides functional aesthetic value that meets their expectations. This research provides important insights for businesses offering nail art services to improve their services based on consumer preferences. This will enhance customer satisfaction and boost market competitiveness.